Jerome's Hebrew philology : a study based on his commentary on Jeremiah - Graves, Michael, 1973- (Supplements to Vigiliae Christianae, 2007)
Describes the practice of Hebrew scholarship in St Jerome and the significance of Hebrew for his biblical exegesis.